The Metamorphosis as a Critique of Enlightenment - Shrestha, Ravi Kumar (Patan Prospective Journal, 2023)
This research article deals with the failure of enlightenment in Gregor Samsa’s life which The Metamorphosis reflects. Enlightenment means the way of enlightening with the help of reasons, logics and skeptical power of knowledge on any subject/discipline. It implies the emancipation from superstitious beliefs through the power of reasons. It can be regarded as the cradle of modernity. Anyway, the God-centered medieval age is converted into the man-centered renaissance age, which is regarded as the beginning of enlightenment in the modern history of mankind. Different theorists of enlightenment believe that human life becomes perfect and social due to reasons. The modern technology and science that are uplifting the lifestyle of human beings is due to the power of reasons. However, the philosophy that reason is the core of human beings becomes a great failure in the life of Gregor Samsa in The Metamorphosis. After Samsa’s physical metamorphosis into a venomous insect, he suffers from alienation, consciousness, and existentialism though he uses his inherent rationalistic power of thinking. Hence, Immanual Kant’s theory of enlightenment can be applied to show the futility of enlightenment due to the effect of modernity. Likewise, Rene Descartes’ theory of existentialism can be applied to show the struggle of an individual despite the effect of modernity for the survival. Thus, for the broad theoretical framework, Kant and Descartes can be used as theorists. Their theory of enlightenment and existentialism can be used for the textual analysis of the select novella to discover that The Metamorphosis is a critique of judgment.